IMPROVEMENT OF OPERATION AND RESEARCH METHODOLOGY OF THE HYDRAULIC FLAKE FORMATION CHAMBER FOR DRINKING WATER SUPPLY - Epoian, S.; Airapetian, T.; Haiduchok, O.; Blahodarna, H.; Volkov, V. (Municipal economy of cities. Series: «Economy science», 2024)
Ukraine’s surface water sources are unsatisfactory due to pollution caused by industrial and agricultural activities and the Russian invasion. As the natural water quality deteriorates, the treatment plant’s efficiency in preparing drinking water for the population’s needs decreases. The hydraulic flake formation chamber allows for physicochemical processes that produce large and solid flakes of metal hydroxides with impurities that quickly settle and are then removed from the water. This study aims to develop a methodology for experimental research on the new design of a swirl-vortex flake formation chamber that intensifies the water purification process in the domestic and drinking water supply systems. The proposed design of the swirl-vortex chamber has dimensions of 0.75×2.0 m and a height of 0.65 m. Due to the installation in the first section of 4 fittings with nozzles, two pieces on each pipe, and in the second section, six fittings with nozzles, three pieces on each pipe with a diameter of 6–10 mm, it is possible to increase the effect of water illumination. The authors performed hydraulic modelling following the Reynolds criterion (Re) and the Froude criterion (Fr). We conducted experiments using artificial turbidity water. White-blue clay was used as a turbidant because it contains more small particles than the white-green one. We decided to model flake formation chambers according to the Froude criterion (Fr). Modelling according to the Reynolds criterion leads to such large velocity gradients that it simply does not make sense to talk about flake formation processes. We carried out the second series of experiments to obtain a qualitative assessment of the swirl-vortex chamber’s work in forming flakes by studying the deposition of flakes at different velocity gradients and angles of inclination of the nozzles. The best effect of lightening the water in the flake formation chamber occurs at a nozzle inclination angle of 45° to the bottom. The best effect of water clarification happens at a velocity gradient of about 60 s-1 and the water residence time in the flake formation chamber of 200–300 s.